Traumatic Spinal Cord Injury and the Gut Microbiota: Current Insights and Future Challenges - Jogia, Trisha; Ruitenberg, Marc J. (Frontiers in Immunology, 2020)
Individuals with traumatic spinal cord injury (SCI) suffer from numerous peripheral complications in addition to long-term paralysis that results from disrupted neural signalling pathways. Those living with SCI have consistently reported gastrointestinal dysfunction as a significant issue for overall quality of life, but most research has focused bowel management rather than how altered or impaired gut function impacts on the overall health and wellbeing of the affected individual. The gut-brain axis has now been quite extensively investigated in other neurological conditions but the gastrointestinal compartment, and more specifically the gut microbiota, have only recently garnered attention in the context of SCI because of their vast immunomodulatory capacity and putative links to infection susceptibility. Most studies to date investigating the gut microbiota following SCI have employed 16S rRNA genomic sequencing to identify bacterial taxa that may be pertinent to neurological outcome and common sequalae associated with SCI. This review provides a concise overview of the relevant data that has been generated to date, discussing current understanding of how the microbial content of the gut after SCI appears linked to both functional and immunological outcomes, whilst also emphasizing the highly complex nature of microbiome research and the need for careful evaluation of correlative findings. How the gut microbiota may be involved in the increased infection susceptibility that is often observed in this condition is also discussed, as are the challenges ahead to strategically probe the functional significance of changes in the gut microbiota following SCI in order to take advantage of these therapeutically.